Product-focused software process improvement : 16th International Conference, PROFES 2015, Bolzano, Italy, December 2-4, 2015 : proceedings /: 16th International Conference, PROFES 2015, Bolzano, Italy, December 2-4, 2015 : proceedings. (2015) - Unknown
No abstract available